Assessment for utilization of tobacco stem ash as a potential supplementary cementitious material in cement-based composites. (1st August 2022) - Khan, Adnan; Ali Sikandar, Muhammad; Tariq Bashir, Muhammad; Azmat Ali Shah, Syed; Zamin, Bakht; Rehman, Khalid
Abstract: Present study investigates the effectiveness of utilizing tobacco stem ash (TSA) as the partial replacement of Portland cement (PC) on the properties of cement pastes and mortars. Cement pastes and mortars were fabricated by replacing cement with TSA at four replacement levels i.e., 3.75, 7.5, 11.25, and 15 wt% relative to cement. Setting time, consistency, and hydration activity tests were performed on TSA-based cement pastes. Moreover, water absorption, porosity, compressive strength, ultrasonic pulse velocity (UPV), and electrical resistivity (ER) testing were performed on TSA-based mortars. The pozzolanic behavior of TSA was assessed via Frattini test and strength activity index. Analytical characterizations such as x-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), thermogravimetric (TG), scanning electron microscopy (SEM), and energy-dispersive x-ray (EDX) analyses were also performed. The results indicate lower water absorption and apparent porosity, leading to enhanced compressive strength, UPV, and ER values for TSA-based mortars. The analytical characterizations show that TSA promotes the hydration reaction and formation of a greater amount of cement hydrates. The strength activity index and Frattini test results showed that TSA possesses moderate pozzolanic activity at a higher replacement level. While, for low replacement levels of TSA in cement composites, the hydration reaction is governed by rapid precipitation of portlandite due to higher hydration activity. Highlights: Tobacco stem ash (TSA) is used as a partial replacement of cement in pastes and mortar. Utilizing TSA promotes the higher hydration rate and improves the mechanical properties of mortars. Utilizing TSA enhances the ultrasonic pulse velocity and electric resistivity of mortars. TSA possesses moderate pozzolanic activity at a higher replacement level.